2010
DOI: 10.1007/s10815-010-9495-3
|View full text |Cite
|
Sign up to set email alerts
|

Assisted hatching in assisted reproduction: a state of the art

Abstract: The World Health Organization estimates that one in six couples experience some delay in conception and an increasing number require treatment by the assisted conception (AC) procedures of in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI).The implantation rate of embryos resulting from in vitro fertilization cycles is generally less than 20%. The exposure of oocytes and embryos to the artificial conditions of in vitro culture may have negative effects on the embryo's ability to undergo no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 84 publications
(95 reference statements)
1
92
1
2
Order By: Relevance
“…It is unclear what the diameter of the complete hatch site was in this study. Another concerning trend in this study was 22% of pregnancies were multiple pregnancies, more than typically seen (Mantoudis et al, 2001), which is not unique to this trial (Hammadeh et al, 2011). In contrast to the findings of Mantoudis et al, Wong et al found improved hatching rates with complete hatching compared to partial hatching, 38% vs. 25%, respectively (Wong et al, 2003).…”
Section: Assisted Hatchingcontrasting
confidence: 59%
See 3 more Smart Citations
“…It is unclear what the diameter of the complete hatch site was in this study. Another concerning trend in this study was 22% of pregnancies were multiple pregnancies, more than typically seen (Mantoudis et al, 2001), which is not unique to this trial (Hammadeh et al, 2011). In contrast to the findings of Mantoudis et al, Wong et al found improved hatching rates with complete hatching compared to partial hatching, 38% vs. 25%, respectively (Wong et al, 2003).…”
Section: Assisted Hatchingcontrasting
confidence: 59%
“…Ultraviolet wavelengths are close to the absorption wavelength of DNA (260 nm). As a result, these lasers are minimally used in reproductive technologies due to concern for mutagenic effects (Green et al, 1987;Hammadeh et al, 2011;Kochevar et al, 1989). The next generation of lasers were designed to circumvent dangers of UV wavelength and cytotoxicity by emitting wavelengths in the infrared region (>800 nm) (Ebner et al, 2005).…”
Section: History Of Lasers In Ivfmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by the early reports that observed a significant improvement in human embryo implantation rates when assisted hatching (artificial thinning or breaching of the ZP) was attempted [25,26,70,100]. Many assisted reproductive technology (ART) programs have since incorporated the use of assisted hatching in efforts to improve clinical outcomes [47]. However, differences in patient populations, operator experience, hatching technique and study design make it difficult to compare findings from different centers.…”
Section: Zona Pellucidamentioning
confidence: 99%